Subsurface ocean turbulent mixing enhances central Pacific ENSO - Chuanyu Liu; Fan Wang; Armin Köhl; Xiaowei Wang; Chunzai Wang; Kelvin J. Richards (Nature Communications)
Abstract Since the 21st century, the El Niño and Southern Oscillation (ENSO) exhibits more pronounced signals in the central Pacific (CP) rather than the eastern Pacific (EP), but the prediction skill has waned, suggesting limited understanding of crucial dynamics within the prediction framework. The ocean mixing around the mixed layer base, which transfers heat downward in a diabatic manner, was considered a potential influencing factor; yet, its effect has not been adequately examined in either CP or EP regions due to insufficient data. Here, we propose an Argo profile data-based mixing estimation model, which yields abundant estimates of subsurface ocean mixing and turbulent heat flux. Consequently, we find significant positive feedback of the ocean mixing-induced diabatic warming/cooling on the CP ENSO, but not on the EP ENSO. Particularly, the diabatic effect dominates sea surface temperature change in the CP region, highlighting the necessity for diabatic CP ENSO positive feedback dynamics in prediction models.